Comparative Resistance of Bacterial Foodborne Pathogens to Non-thermal Technologies for Food Preservation - Cebrián, Guillermo; Mañas, Pilar; Condón, Santiago (Frontiers in Microbiology, 2016)
In this paper the resistance of bacterial foodborne pathogens to manosonication (MS), pulsed electric fields (PEF), high hydrostatic pressure (HHP) and UV-light (UV) is reviewed and compared. The influence of different factors on the resistance of bacterial foodborne pathogens to these technologies is also compared and discussed. Only results obtained under harmonized experimental conditions have been considered. This has allowed us to establish meaningful comparisons and draw significant conclusions. Among the six microorganisms here considered, Staphyloccocus aureus is the most resistant foodborne pathogen to MS and HHP and Listeria monocytogenes to UV. The target microorganism of PEF would change depending on the treatment medium pH. Thus, L. monocytogenes is the most PEF resistant microorganism at neutral pH but Gram-negatives (Escherichia coli, Salmonella spp., Cronobacter sakazakii, Campylobacter jejuni) would display a similar or even higher resistance at acidic pH. It should be noted that, in acidic products, the baroresistance of some E. coli strains would be comparable to that of S. aureus. The factors affecting the resistance of bacterial foodborne pathogens, as well as the magnitude of the effect, varied depending on the technology considered. Inter- and intra-specific differences in microbial resistance to PEF and HHP are much greater than to MS and UV. Similarly, both the pH and aw of the treatment medium highly condition microbial resistance to PEF and HHP but no to MS or UV. Growth phase also drastically affected bacterial HHP resistance. Regarding UV, the optical properties of the medium are, by far, the most influential factor affecting its lethal efficacy. Finally, increasing treatment temperature leads to a significant increase in lethality of the four technologies, what opens the possibility of the development of combined processes including heat. The appearance of sublethally damaged cells following PEF and HHP treatments could also be exploited in order to design combined processes. Further work would be required in order to fully elucidate the mechanisms of action of these technologies and to exhaustively characterize the influence of all the factors acting before, during and after treatment. This would be very useful in the areas of process optimization and combined process design.